Exploring Keebet von Benda-Beckmann's Legal Pluralism in Slum Transformation: An Ethnographic Study of Urban Revitalization in Indonesia - Koeswahyono, Imam; Maharani, Diah Pawestri; Rahmawati, Nadyah Maylika; Ismudyahwati, Ika (UI Scholars Hub, 2024)
Slum areas in Indonesia present a significant challenge, with government programs such as the National Slum Upgrading Program (NSUP) aiming to address urban poverty and improve living conditions. Despite the implementation of formal policies, the interplay between legal frameworks and local practices often determines the success of such initiatives. Drawing on Keebet von Benda-Beckmann’s theory of legal pluralism, this research examines the transformation of slums into productive and sustainable zones, focusing on Kampung Jodipan, Kampung Heritage Kajoetangan, and Kampung Kreatif Dago Pojok. These case studies reveal how formal legal systems interact with informal norms and community-driven practices in achieving urban revitalization. Using an ethnographic approach, the study employed in-depth interviews, participant observation, and analysis of legal documents to explore the dynamic collaboration between government, private stakeholders, and local communities. The findings indicate that while government-led initiatives like the NSUP provide vital resources and frameworks, the integration of informal community norms and active local participation plays a pivotal role in the success of slum transformation projects.This research concludes that sustainable urban development requires a balance between formal policies and grassroots efforts. The coexistence of multiple legal systems, as framed by Keebet von Benda-Beckmann’s legal pluralism, offers a critical lens to understand how collaborative governance can address urban poverty. The study emphasizes the importance of culturally embedded, adaptive approaches that bridge formal and informal systems to create inclusive and sustainable urban spaces.